On the Discourse of History. For an Episteme of Historical Knowledge - Sevillano, Francisco (2021)
This paper takes stock of the theoretical debate on the role of discourse in historical work. In the first part of the study, the notion of discourse is defined under the approach known as «linguistic turn» since the 1960s. In particular, the main features of this approach are described in light of the narrative and anti-realist assumptions of the «new philosophy of history» and their reassessment under the «experiential turn». The second part of the paper refutes these assumptions and argues about the cognitive value of history from its classical origins.